Kikuchi Fujimoto Disease - Jamal, Al-Bishri (Libertas Academica, 2012)
In order to determine the clinical significance of Kikuchi Fujimoto Disease (histiocytic necrotizing lymhadenitis) and to review the literature available on this condition, we selected the Medicine research papers in English language published between the years 1972 to 2011. Kikuchi Fujimoto Disease (KFD) is an uncommon, cosmopolitan, benign and self-limiting condition with higher Japanese and Asian prevalence. Most of the sufferers of KFD are young people who seek treatment because of having acute tender cervical lymphadenopathy, low grade fever and night sweats. Coagulative necrosis with ample karyorrhetic debris in paracortical areas of the involved lymph nodes is the characteristic histologic feature of KFD. Diagnosing KFD is crucial as it can be mistaken for malignant lymphoma and SLE. KFD was put forth first time in 1972 by Dr. Masahiro Kikuchi and by Funimoto as lymphadenitis with reticular proliferation, histiocytes and abundant nuclear debris. It is a rare benign condition of lymph nodes and most of the clinicians and pathologists are unfamiliar with it. KFD is self-limiting disease (within 1 to 4 months), however, patients should be followed up regularly as it may crop up again or progress to SLE. Analgesics and antipyretics help to ameliorate the symptoms.